2016
DOI: 10.1186/s12894-016-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

[−2]proPSA versus ultrasensitive PSA fluctuations over time in the first year from radical prostatectomy, in an high-risk prostate cancer population: A first report

Abstract: Background[−2]proPSA and its derivatives have an higher diagnostic accuracy than PSA in predicting prostate cancer (PCa). In alternative to PSA, ultrasensitive PSA (uPSA) and [−2]proPSA could be potentially useful in recurrent disease detection. This research focused on [−2]proPSA and uPSA fluctuations over time and their possible clinical and pathological determinants, in the first year after RP.MethodsA cohort of 106 consecutive patients, undergoing RP for high-risk prostate cancer (pT3/pT4 and/or positive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…We found that only PSA was able to correlate with BCR at the first (AUC 0.64; p-value 0.03) and third month (AUC 0.72; p-value 0.0004) after RP and all other markers tested such as fPSA, %fPSA, hK2, hK2/fPSA, hK2/%fPSA, [-2]proPSA and PHI were devoid of any predictive value (p-value>0.05). Similar findings were obtained by S. De Luca et al [23] who tested [-2]proPSA in a group of high-risk patients at 3-month intervals in the first year after RP. Conversely, Casale et al [24] concluded that [-2]proPSA could be of use in detecting recurrence earlier than standard PSA in a cohort of 134 patients after RP with a follow up of three years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that only PSA was able to correlate with BCR at the first (AUC 0.64; p-value 0.03) and third month (AUC 0.72; p-value 0.0004) after RP and all other markers tested such as fPSA, %fPSA, hK2, hK2/fPSA, hK2/%fPSA, [-2]proPSA and PHI were devoid of any predictive value (p-value>0.05). Similar findings were obtained by S. De Luca et al [23] who tested [-2]proPSA in a group of high-risk patients at 3-month intervals in the first year after RP. Conversely, Casale et al [24] concluded that [-2]proPSA could be of use in detecting recurrence earlier than standard PSA in a cohort of 134 patients after RP with a follow up of three years.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, besides one study comparing the trends of [-2]proPSA and uPSA in the first year after RP in a high-risk population [23], and a second study [24] comparing the kinetics of [-2]proPSA and PSA in the first 3 years post-RP, no recent studies exist on the potential use of markers such as fPSA, %fPSA, hK2 and PHI to predict BCR and identify disease persistence (DP) in the postoperative setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, tissue biopsy is invasive, and the predicted accuracy of PSA should be furthermore improved. Therefore, PSA has been steadily discouraged from being advised in recent years ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%